Philosophical Pursuits in Dance Practice of the 21st Century: Body Concepts - Maria Kozeva; Galina Brandt (Changing Societies & Personalities, 2018)
The art of performance dance in the 20th century is undergoing a transformation involving values, concepts, and styles that are quite distinct from the traditional principles of classical art dance. This turn, beginning around the middle of the 20th century, has found expression in a “radical shift” in terms of the form and content of dance, affecting its components, nature, and purpose; therefore, it is not surprising that the quest for new conceptual foundations acquired its own outlook not only, and not so much in art criticism as in philosophical terms. It can be said that the epicentre of these shifts was a new understanding of the dancing body itself. The diversity of practices – dance theatre, physical theatre, dance performance, non-dance movement, postmodern dance, contemporary dance – have in turn become ways of embodying these new bodily concepts. Of course, the primary results of this quest have had a non-verbal character; nevertheless, in general terms, the level of “conversation” allows us to perceive the philosophical concepts underlying the discoveries made.